Response of Zakat Institutions to Financial Technology as a Strategy in Optimizing Zakat Collection - Fadilah, Sri; Rosdiana, Yuni; Sundaya, Yuhka; Maemunah, Mey; Fitriah, Epi; Lestari, Rini; Hartanto, Rudy (AIBPM Publisher, 2023)
The realization of the large potential of zakat funds is not maximum and has become the background of this research. This shows that the optimization of zakat collection is still low. Many factors have caused this, including the adaptation and implementation of digital zakat, especially financial technology (fintech). The purpose of this research is to determine the use of financial technology in a zakat institution, especially to optimize the collection of ZIS funds. There are still many obstacles to the utilization of digital zakat for zakat institutions. On the other hand, there are many benefits from the adaptation and implementation of digital zakat, especially fintech, including strengthening zakat governance, optimizing zakat collection and others. For this reason, it is very important to examine the response of zakat institutions to financial technology to optimize zakat collection. The research method used is a case study method with a descriptive analysis research approach at BAZNAS Jawa Barat. Data collection techniques: documentation and interviews. The results show that the implementation of fintech at BAZNAS Jawa Barat is essential due to the rapid technological changes and the Covid 19 pandemic in 2020. Its effectiveness is very good that affects on the increase ofÂ ZIS fundraising from 2018 to 2021.